2014
DOI: 10.1167/iovs.14-15278
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Analysis of the Normal Anatomy of the Aging Fovea

Abstract: Normal foveal anatomical configuration changes with age. Normal aged foveas are less symmetric along midline with steeper slopes. Differentiating between normal aging and pathologic changes using SD-OCT scans may allow early diagnosis, follow-up, and better management of the aging population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 23 publications
6
17
1
Order By: Relevance
“…Older eyes have been reported to have a sharper slope, however a preserved total volume has been reported. 29 This finding is consistent with our results because a reduced radius with a preserved maximum thickness implies a steeper slope in the foveal shape. Our data does not support differences in axial length being responsible for this observation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Older eyes have been reported to have a sharper slope, however a preserved total volume has been reported. 29 This finding is consistent with our results because a reduced radius with a preserved maximum thickness implies a steeper slope in the foveal shape. Our data does not support differences in axial length being responsible for this observation.…”
Section: Discussionsupporting
confidence: 93%
“…28 Furthermore, it has been reported that aged fovea are more asymmetric than younger fovea. 29 In the present study, we found that none of the three measured parameters were affected by ageing, however, the radius showed a tendency to be shorter in older participants. Older eyes have been reported to have a sharper slope, however a preserved total volume has been reported.…”
Section: Discussioncontrasting
confidence: 47%
“…Only 57% of subjects performing better at detecting the direction of motion with the system ON than OFF. The clinical trial also reported improved orientation and mobility with the system, but other studies have reported the opposite, with a statistically significantly worsened performance at spatial orientation tasks with the implant turned on [147]. One reason the Argus II implant could degrade spatial orientation could be the fact that visual percepts it delivers are unrelated to direction of gaze.…”
Section: Clinical Resultsmentioning
confidence: 94%
“…For example, in the case of the macula, several studies and approaches have already been published in order to provide a better insight into the definition of healthy structure and shape. [1][2][3][4][5] ONH represents the part in which all retinal ganglion cell axons gather to leave the eye toward the brain. As such, investigating the ONH is central to the diagnosis of many disorders affecting the optic nerve like glaucoma, 6 idiopathic intracranial hypertension (IIH), 7,8 optic neuritis (ON), 9,10 and optic neuropathies of other etiology, for example, in the context of multiple sclerosis (MS) or neuromyelitis optica spectrum disorders (NMOSD).…”
Section: Introductionmentioning
confidence: 99%